Synthesis of 1,3,4-Oxadiazole Derivatives from Ethyl-2-Piperidone-3-Carboxylate - M. A. Sheat; O. I. Mohammed (College of Education for Pure Sciences, 2012)
ABSTRACT In the present work, some new 1,3,4- Oxadiazole derivatives have been synthesized from Ethyl-2-Piperidone-3-Carboxylate. The reaction of the ethyl ester with hydrazine hydrate afforded the corresponding hydrazide (I). Treatment of the latter compound with different aromatic aldehydes yielded a new hydrazones (II). Preparation of 1,3,4- Oxadiazoles (III) have been achieved by oxidative cyclization of hydrazones (II) by the use of lead dioxide in glacial acetic acid. The structural formula of the synthesized compounds were established by physical and spectral methods.